A two-stage process for conversion of brewer’s spent grain into volatile fatty acids through acidogenic fermentation - Guarda, Eliana C. (2021)
This work is focused on the valorization of brewer’s spent grains (BSG) into volatile fatty acids (VFA) through acidogenic fermentation. VFAs are building blocks for several applications, such as bioplastics’ production. Using acid hydrolysis as pre-treatment, several batch assays were performed and the impact of organic load (OL) and pH on VFA production from BSG hydrolysate was assessed. Regardless of the condition, the produced acids were mainly butyric and acetic acids followed by propionic acid. The OL had a direct impact on the total organic acid concentration with higher concentrations at the highest OL (40 gCOD L-1). pH affected the concentration of individual organic acid, with the highest fermentation products (FP) diversity attained at pH 5.0 and OL of 40 gCOD L-1. To assess the potential application of organic acids for biopolymers (such as polyhydroxyalkanoates) production, the content in hydroxybutyrate (HB) and hydroxyvalerate (HV) monomers was estimated from the respective precursors produced at each pH and OL. The content in HV precursors increased with pH, with a maximum at pH 6.0 (ca. 16% C-mol basis). The acidogenic fermentation of BSG hydrolysate was also assessed in continuous operation, using an expanded granular sludge bed reactor (EGSB). It was shown that the BSG hydrolysate was successfully converted to VFAs without pH control, achieving higher productivities than in the batch operation mode.